2022
DOI: 10.1111/jog.15254
|View full text |Cite
|
Sign up to set email alerts
|

Systemic immune‐inflammation index to predict placenta accreta spectrum and its histological subtypes

Abstract: Aim: In this study, we aimed to investigate the role of systemic immune-inflammation index (SII) and other inflammatory parameters in the diagnosis of placenta accreta spectrum (PAS) and its histological subtypes. Methods: This retrospective case-control study included patients who underwent surgery for placenta previa (PP). Case group (patients with PAS) included pregnant women diagnosed with histologically confirmed PAS, whereas control group (patients with PP) included pregnant women who underwent cesarean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 33 publications
0
1
0
Order By: Relevance
“…Oxidative stress, hypoxia, ischemia, and tissue necrosis of the placenta are associated with endothelial cell activation and maternal inflammatory responses. Various innate and adaptive immune cells and mediators play a role in this process 12,13 . Regulatory T cells, macrophages, natural killer cells and neutrophils are known to contribute to preeclampsia, but other immune cells such as B cells, inflammatory cytokines and autoantibodies directed against the angiotensin II type 1 receptor have also been recently discovered 13 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oxidative stress, hypoxia, ischemia, and tissue necrosis of the placenta are associated with endothelial cell activation and maternal inflammatory responses. Various innate and adaptive immune cells and mediators play a role in this process 12,13 . Regulatory T cells, macrophages, natural killer cells and neutrophils are known to contribute to preeclampsia, but other immune cells such as B cells, inflammatory cytokines and autoantibodies directed against the angiotensin II type 1 receptor have also been recently discovered 13 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition to activating the immunological cascade that leads to the development of pre-eclampsia, the immunological balance plays a key role in the remodeling of the spiral artery. Studies have shown that disruption of the low flow resistance of the spiral artery affects the histologic structure of the placenta to some extent 11,12 .…”
Section: Introductionmentioning
confidence: 99%
“…[26] It was used in the evaluation of pathologies such as placental anomalies, hyperemesis gravidarum, and peripartum cardiomyopathy during pregnancy and it was found to be significantly higher. [27][28][29] There is no study in the literature examining the relationship between SII and AA. In their study, Telaferli and colleagues found that the increase in SII level was more pronounced in patients with complicated AA than in patients with uncomplicated AA who were not pregnant.…”
Section: Discussionmentioning
confidence: 99%
“…Both NLR and PLR have been shown to be correlated with cancer and several inflammatory diseases, and have begun being regarded as likely inflammatory markers [6][7]. The system immune-inflammation index (SII), used as a novel inflammatory biomarker in recent years, has been shown to be associated with adverse obstetric outcomes such as placental pathologies [8][9]. To the best of our knowledge, there have been no reports to date of the importance of the SII in women with IO in the first trimester.…”
Section: Introductionmentioning
confidence: 99%